Everyday speculation in the remaking of peri-urban livelihoods and landscapes. (March 2023) - Leitner, Helga; Nowak, Samuel; Sheppard, Eric
Peri-urbanization is transforming the urban-rural interface of metropolitan areas across the global south. Large-scale planned developments and infrastructure projects result in the widespread displacement of residents and the disappearance of agricultural fields, vegetable plots, and small enterprises. Through multi-year fieldwork in eastern peri-urban Jakarta, we shift the optic from the large players driving these transformations—developers, land brokers, and investors—to examine how residents of peri-urban settlements (kampungs) respond to unexpected developments and manage the uncertainties associated with market-induced displacement. We conceptualize their practices as everyday speculation, extending speculation beyond its financial meaning to include social and cultural aspects. Both displacees in relocation kampungs and holdouts in kampungs subject to displacement make the most of emergent spatiotemporal rent gaps to devise ways to improve their livelihoods and accumulate wealth, but they also attempt to realize their social and cultural aspirations of reproducing kampung ways of life characterized by dense social networks and commoning practices such as mutual aid. Speculation reinforces pre-existing economic inequalities among kampung residents but is not obliterating social and cultural values that contest the norms of neoliberal global urbanism. Scaling up from everyday speculation by individual households, we identify three paths of kampung transformation that are concatenating across a shape-shifting speculative kampung landscape that coexists in a complex and synergistic relationship with the planned developments. Understanding residents' everyday actions is thus important to grasping the full scope of peri-urbanization.